Baptists in America - Leonard, Bill (Bill J.) (Columbia contemporary American religion series., 2005)
Offers a historical and sociological portrait of this diverse denomination. Traces the history of Baptists, examines the development of Baptist beliefs and practices, and offers an overview of the various denominations and fellowships within Baptism. Also discusses theological disputes, as well as social and political divisions among Baptists.